The Determinant Factors of Students’ Green Behavior: Lesson from Indonesia - Suratno Suratno (Faculty of Economics, State University of Jakarta., 2020)
This study aims to examine the determinants factors affecting students’ green behavior, particularly in plastic waste problems. The subjects of this study were Jambi University students with a sample of 1001 respondents. Data collection instruments were compiled by the researcher and tested for validity and reliability. Data collection was carried out using online questionnaire in collaboration with the information technology and communication development institute of the University of Jambi. The collected data is analyzed quantitatively using regression analysis by employing SPSS (version 25. The findings of the study showed that student awareness in environmental issues is the main variable influencing student behavior, followed by students’ understanding of environment variables and ecological-economic literacy variables. Meanwhile, the student lifestyle variable does not affect the behavior of students in the plastic waste problem.